Disability, work and income: a British perspective - Elena Bardasi; Stephen P. Jenkins; John A. Rigg (University of Essex, Institute for Social and Economic Research (ISER), 2000)
This paper analyses the economic impact of becoming disabled for British working-age men. The data is from the five eight waves (1991/8) of the British Household Panel Survey (BHPS). Cross-sectional evidence shows that the income of disabled working-age men is substantially lower than non-disabled working-age men. However, analysis of longitudinal data indicates that the majority of this disadvantage is accounted for by the low economic status of the men who became disabled. These findings for British men are consistent with similar evidence for US and German men. A major cross-national difference is that becoming disabled is associated with a much greater outflow from employment for working-age men in Britain compared to the USA or Germany.
Keywords: 330